Macroeconomic Variables and Unemployment: The Case of Turkey - Taylan Taner Doğan (International Journal of Economics and Financial Issues, 2012)
This study investigates the response of unemployment to selective macroeconomics shocks over period of 2000:Q1-2010:Q1. It is found that positive shocks to growth, growth in export and and inflation reduce unemployment. On the other hand, shocks to exchange rate, interbank interest rate and money supply increase unemployment. Our results are consistent with Phillips curve and Okun’s Law suggestion. Namely, negative relationship between output and unemployment and positive relationship between unemployment and inflation are found. Also, this study found consistent results with earlier literature.